DABCO-Catalyzed α-Regio- and Diastereoselective (3+2) Cycloadditions of Nitrone Ylides from Isatins and Activated Alkenes - Cheng, Xiangsheng; Fei, Weihong; Luo, Zihao; Li, Jianjun; Wang, Zhen; Yao, Weijun (Synthesis, 2020)
α-Regio- and diastereoselective (3+2) cycloadditions of nitrone ylides derived from isatins with activated alkenes have been demonstrated. This mild protocol allows rapid access to a wide range of 3′,5′-diaryl-1′-hydroxy-2-oxospiro[indoline-3,2′-pyrrolidine] derivatives by using DABCO as an efficient catalyst. This method could also be carried out through three-component reaction efficiently in good yields and excellent diastereoselectivity.
Keywords: nitrone ylide; cyclization; spirooxindole; regioselectivity; diastereoselectivity; isatin